Pendekatan Terkini Dan Masa Depan Pada Penyakit Jantung Koroner Prematur - Firdaus, Achmad Jauhar; Satrijo, Budi (RSUD Dr. Saiful Anwar Province of East Java, 2025)
Coronary artery disease is one of the most frequent cardiovascular diseases and has consistently ranked as the leading cause of death globally for the past three decades. During that period, trends regarding coronary artery disease in young adults have exhibited a complicated interaction of rising incidence and mortality rates in particular populations. Coronary artery disease encompasses a broad range of symptoms and is particularly concerning when it develops at a young age, typically before 55 years in men and 60 years in women. The disease spectrum varied from asymptomatic conditions to chronic symptoms known as chronic coronary syndrome and acute symptoms known as acute coronary syndrome. Multiple recommendations and consensus have been established concerning the approaches to these spectrums, although there is less discourse on precisely addressing the young population's specific requirements. This extensive analysis offers insights into premature coronary artery disease and the multidimensional approach based on the latest guidelines and the novel approach using the help of artificial intelligence and machine learning, emphasizing early detection and diagnosis across the whole clinical spectrum.